Versatile Vidyasagar: A Superior Scholar, Modern Philosopher, Real Educationist & True Social Reformer - Mahato, Ujjwal; Murmu, Dilip Kr. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
In the period of the 19th century, India has given birth to a starlike personality in the name of Ishwar Chandra Bandopadhyay. He was a real hero and down to earth in his habit. He dedicated his life for draw out the nation to light from the darkness. He was a polymath, educator, social reformer, writer, and philanthropist. He was one of the greatest intellectuals and activists of the 19th century and one of the pillars of the Bengal Renaissance who had given a shape and direction. Above All, he is a strong symbol of a versatile personality. He is called in the name of Vidyasagar (The Ocean of Knowledge) and Dayarsagar (The Ocean of Kindness) for her dignified thoughts and works. Researchers have highlighted the versatility of Ishwar Chandra Vidyasagar in their theoretical research. From their research, Vidyasagar will be known as such a meritorious student; Similarly, there will be an opportunity to know Vidyasagar's philosophical thoughts, educational thoughts, social reform, responsibility towards women's education, etc.